Extranodal nasal-type NK/T-cell lymphoma of the palate and paranasal sinuses - Nikolaos, Nikitakis (International Scientific Literature, Inc., 2012)
BACKGROUND: Extranodal nasal-type natural killer (NK)/T-cell lymphoma represents a rare entity, typically originating in the nasal cavity, palate or midfacial region. Signs and symptoms include non-specific rhinitis and/or sinusitis, nasal obstruction, epistaxis, facial swelling and development of deep necrotic ulceration in the midline of the palate, causing an oronasal defect. Differential diagnosis includes fungal infections, Wegener’s granulomatosis, tertiary syphilis, other non-Hodgkin’s lymphomas and malignant epithelial midline tumors. CASE REPORT: We present a case of a 40-year-old man complaining of headache, facial pain, nasal congestion and fever. Examination revealed a large deep necrotic ulcer in the middle of the palate, presenting as an oronasal defect. Endoscopic rhinoscopy revealed crusts in the nasal cavities, moderate perforation of the nasal septum cartilage and contraction of the middle and inferior conchae. Computer tomography showed occupation of the maxillary sinuses, ethmoidal cells and sphenoidal sinus by a hyperdense soft tissue mass. Laboratory investigation revealed increased erythrocyte sedimentation rate. A wide excision of the lesion was performed. Histopathological and immunohistochemical evaluation established the diagnosis of extranodal nasal-type NK/T-cell lymphoma. The patient was treated with CHOP chemotherapy, involved-field radiotherapy and autologous bone marrow transplantation. A removable partial denture with obturator was fabricated and inserted to relieve problems caused by the oronasal defect. CONCLUSIONS: Extranodal nasal-type NK/T-cell lymphoma is a very aggressive, rapidly progressing malignant neoplasm with a poor prognosis, which can be improved by early diagnosis and combined treatment.